Weaknesses in Emergency Remote Teaching in Higher Education Within the Context of the ODL Learning Component in Turkey - Genç, Hakan; Kesim, Mehmet (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
In critical situations caused by crises such as a pandemic, emergency remote teaching (ERT) practices might not be effective because they depend mostly on on-the-spot decision-making. On the other hand, open and distance learning (ODL) has its own dynamics and is a well-planned system. In order to put quality ODL plans into practice in crisis situations, contingency plans, created before any crises, are required. Past crises ought to be examined in order to cope with future crises effectively. This study aims to identify weaknesses in ERT practices in higher education within the context of the learning component of ODL system by focusing on COVID-19 and using it as an example of a past crisis. Exploratory case study was the method used. The study group consisted of 14 faculty and 14 learners from 14 higher education institutions. Qualitative data were collected via semi-structured interviews and documents. The data were analyzed using descriptive and content analysis. Research findings revealed that ERT has many weaknesses in several themes within the context of the learning component of the ODL system; these include teaching method, course structuring, and e-learning materials, among others. In light of the findings, it can be concluded that many factors influence challenges in ERT. Accordingly, to be able to move from ERT to ODL in the next crisis, these weaknesses need to transform into solutions in advance.